Adaptive joint tracking approach of system parameters and the time delay - Pupeikis, Rimantas (Lietuvos matematikos rinkinys, 2017)
The problem of adaptive joint parameters and the time delay tracking is tackled by processing of input-output observations, when nonstacionary dynamical system has an unknown time delay. The recursive approach based on the method of corrective operators is developed for their tracking. Applicability of algorithms is supported by simulation tests on a computer.